A Short-Term High-Fat Diet Alters Glutathione Levels and IL-6 Gene Expression in Oxidative Skeletal Muscles of Young Rats - Andrich, David E.; Melbouci, Lilya; Ou, Ya; Auclair, Nickolas; Mercier, Jocelyne; Grenier, Jean-Christophe; Lira, Fábio Santos; Barreiro, Luis B.; Danialou, Gawiyou; Comtois, Alain-Steve; Lavoie, Jean-Claude; St-Pierre, David H. (Frontiers in Physiology, 2019)
Obesity and ensuing disorders are increasingly prevalent worldwide. High-fat diets (HFD) and diet-induced obesity have been shown to induce oxidative stress and inflammation while altering metabolic homeostasis in many organs, including the skeletal muscle. We previously observed that 14 days of HFD impairs contractile functions of the soleus (SOL) oxidative skeletal muscle. However, the mechanisms underlying these effects are not clarified. In order to determine the effects of a short-term HFD on skeletal muscle glutathione metabolism, young male Wistar rats (100-125 g) were fed HFD or a regular chow diet (RCD) for 14 days. Reduced (GSH) and disulfide (GSSG) glutathione levels were measured in the SOL. The expression of genes involved in the regulation of glutathione metabolism, oxidative stress, antioxidant defence and inflammation were measured by RNA-Seq. We observed a significant 25% decrease of GSH levels in the SOL muscle. Levels of GSSG and the GSH:GSSG ratio were similar in both groups. Further, we observed a 4.5 fold increase in the expression of pro-inflammatory cytokine interleukin 6 (IL-6), but not of other cytokines or markers of inflammation and oxidative stress. We hereby demonstrate that a short-term HFD significantly lowers SOL muscle GSH levels. This effect could be mediated through the increased expression of IL-6. Further, the skeletal muscle antioxidant defence could be impaired under cellular stress. We surmise that these early alterations could contribute to HFD-induced insulin resistance observed in longer protocols.